Survey Of Sports And Health Physical Education Facilities And Infrastructure - Kharozim, Ahmad; Kusmawati, Wiwik; Lufthansa, Luthfie (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this study was to determine the availability of sports and health education facilities and infrastructure at MTs. Miftahul Ulum Timbuan. This type of research is a survey with descriptive quantitative research methods, the population in this study is MTs. Miftahul Ulum Timbuan. Based on the data analysis that has been done, it can be concluded that there are inadequate facilities and infrastructure for sports and health education at MTs. Miftahul Ulum Timbuan, namely basketball equipment in very poor category with a percentage of 16.67%, and gymnastics equipment in the poor category. once with a percentage of 12.5%, while for adequate facilities, namely volleyball equipment in the medium category with a percentage of 50%, football equipment in the good category with a percentage of 66.67%, athletic equipment in the very good category with a percentage of 100%. For existing infrastructure at MTs. Miftahul Ulum Timbuan, there are volleyball courts, takraw courts, and table tennis courts.